Usage-based and typological approaches to linguistic units - Ono, Tsuyoshi; Laury, Ritva; Suzuki, Ryoko (Benjamins current topics,, 2021)
"The chapters in this volume focus on how we might understand the concept of 'unit' in human languages. It is an analytical notion that has been widely adopted by linguists of various theoretical and applied orientations but has recently been critically examined by both typologically oriented and interactional linguistics. This volume contributes to and extends this discussion by examining the nature of units in actual usage in a range of genetically and typologically unrelated languages, English, Finnish, Indonesian, Japanese, and Mandarin, engaging with fundamental theoretical issues. The chapters show that categories originally created for the description of Indo-European languages have limited usefulness if our goal is to understand the nature of human language in general. The authors thus question the status of traditionally accepted linguistic units, especially their static understanding as a priori entities, and suggest instead that an emergent and interactional view of both structure and function offers a better fit with the data from the languages examined. Originally published as special issue 43:2 (2019) of Studies in Language"--